Corymbia and Eucalyptus essential oils with insecticide activity to Ascia monuste and its selectivity to two non-target organisms - Ribeiro, Arthur Vieira (2017)
Due to an increase in environmental and health issues because of the excessive use of synthetic pesticides, many studies are being developed in order to select plant essential oils (EOs) for pest control. These compounds are pointed as safe control agents, since they have low toxicity to non-target organisms and are non-persistent in the environment. Thus, this study was carried out with the aim to select potential EOs from plants of the Myrtaceae family for the control of Ascia monuste and to evaluate their selectivity to two non-target organisms (Solenopsis saevissima and Tetragonisca angustula). Twelve EOs, extracted by hydrodistillation from Corymbia and Eucalyptus plants, were tested in this study. The terpenes 1,8-cineole, α-pinene, citronellal, ρ-cymene, α-eudesmol and α-phellandrene were the most common compounds (identified by GC-MS/FID). All toxicity bioassays were performed by topical application. C. citriodora EO had the highest insecticidal activity against A. monuste (LD 50 = 20.61 μg. mg -1 ), and also presented a fast action (LT 50 < 10 minutes). Citronellal was the main compound of C. citriodora EO (86.8% of the oil constitution) and exhibited toxicity similar to this EO (LD 50 = 22.44 μg. mg -1 ). Hence, the toxicity of the C. citriodora EO is mostly explained by the citronellal activity. This EO was selective in favor of the predatory ant S. saevissima but caused high mortality of the pollinator bee T. angustula. Therefore, C. citriodora EO is a promising model to the development of insecticides against A. monuste. However, its application must rely on the principles of ecological selectivity, aiming to mitigate its impact over pollinators.